1996
DOI: 10.1021/bi952469q
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Conformation, Hydrophobicity, and Model Membrane Interactions of Diphtheria Toxin to Those of Formaldehyde-Treated Toxin (Diphtheria Toxoid):  Formaldehyde Stabilization of the Native Conformation Inhibits Changes That Allow Membrane Insertion

Abstract: Toxoids are inactivated protein toxins that are used in vaccines. The behavior of diphtheria toxin reacted with formaldehyde (diphtheria toxoid) was compared to that of diphtheria toxin in order to understand the nature of the changes that occur in toxoids upon protein reaction with formaldehyde. Despite the intramolecular cross-links in the toxoid, the conformations of the toxoid and the toxin were very similar in both the native and low pH-induced membrane-penetrating states as judged by fluorescence and hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 35 publications
4
20
1
1
Order By: Relevance
“…Formalinization was found to cause small and large conformational changes in BSA and RNase, respectively. Paliwal and London (1996) showed that conformation of the diphtheria toxoid was stabilized by formalinization, and was similar to that of native toxin as judged by fluorescence and hydrophobicity properties. In a formaldehyde fixation study, Mason and O'Leary (1991) reported that the secondary structures of isolated proteins (BSA, RNase A, and hemoglobin) were retained as determined by calorimetry and infrared spectroscopy.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Formalinization was found to cause small and large conformational changes in BSA and RNase, respectively. Paliwal and London (1996) showed that conformation of the diphtheria toxoid was stabilized by formalinization, and was similar to that of native toxin as judged by fluorescence and hydrophobicity properties. In a formaldehyde fixation study, Mason and O'Leary (1991) reported that the secondary structures of isolated proteins (BSA, RNase A, and hemoglobin) were retained as determined by calorimetry and infrared spectroscopy.…”
Section: Discussionmentioning
confidence: 89%
“…This initial study suggested that, under suitable conditions, fundamental concepts of formaldehyde chemistry with protein antigens could be applied to elucidating the reactivity of formalinized antigens after preparation. If confirmed, the hypothesized FMAP could have significant implications in the basic and applied biological sciences, particularly with regard to the study of: (a) antigen stability in controlled release polymers (Schwendeman et al, 1995); and (b) antigen-biochemical interactions (e.g., those occurring during antigen uptake in cell membranes) (Paliwal and London, 1996). However, in the previous study, the aggregation of a nonformalinized antigen control was not assessed (Schwendeman et al, 1995), and the question of whether the FMAP is specific to TT or to any other formalinized antigens warrants further investigation.…”
Section: Introductionmentioning
confidence: 83%
“…This presumably arises from intramolecular cross-linking. 9 For direct ELISA, coating of the microtiter plate wells was performed with RNase A dissolved in PBS. The antigen, immobilized via hydrophobic interaction with the polystyrene surface, was then incubated with a rabbit anti-RNase A:HRP-conjugated antibody.…”
Section: Resultsmentioning
confidence: 99%
“…A low pH-induced folding of native proteins to the molten globule state where the secondary structure is retained but the tertiary structure is disrupted leading to exposure of hydrophobic sites has been detected in number of proteins (38,39). More recently independent studies in the case of DT have also suggested the formation of molten globule state at low pH (40,41). That a molten globule state may be involved in promoting insertion of soluble proteins in membranes has also been proposed earlier (42,43).…”
Section: Fig 6 Radioactivity and Mass Release On Edman Degradation mentioning
confidence: 63%